International Humanitarian Law and Banned Ammunition - Helnarska, Karolina; Motrycz, Grzegorz (Roczniki Nauk Społecznych, 2026)
This article aims to (1) outline the historical development of small-arms projectiles criticised for causing excessive injury or unnecessary suffering; (2) present the evolution of key international humanitarian law norms restricting the use of bullets that expand or deform in the human body; (3) compare, in a controlled ballistic gelatin experiment, the damage pattern produced by a full metal jacket projectile (FMJ) and an open-tip match/HPBT projectile (Lapua Scenar) in calibre .308 Win. (7.62×51 mm). The analysis was placed in the broader context of MPH regulations concerning the use of firearms as a means of combat (including the principles of proportionality), which allows the assessment of ammunition design to be linked to the manner in which it is used. The objectives and hypotheses adopted by the authors should assist the reader in an analysis leading to a comprehensive understanding of the munitions issue and its impact in both the legal and military (tactical operations) fields.